Research on Impoliteness Strategies and Identity Construction in a Dream of Red Mansions - Dong, Tian; Qiu, Lu (International Journal of Publication and Social Studies, 2019)
In daily interactions between people, conflicting discourse is inevitable due to differences in values, education level, and life experience. Because these conflicting discourses are deliberate, contradictory and negative, it is impolite for the listener. Intentional impoliteness is a special pragmatic strategy based on specific communicative intentions. The dialectical relationship between impoliteness and identity construction has become one of the hot issues of research. The dialectical relationship between impoliteness and identity construction has become a hot issue in current linguistic research. Guided by J. Culpeper’s Impoliteness Theory, this paper explores how impoliteness is performed and worked in Chinese context from two aspects: impoliteness strategy and identity construction. The impoliteness strategy consists of Bold on record impoliteness, Positive impoliteness, Negative impoliteness, Sarcasm/Mock Politeness and Withhold Politeness. It is revealed that impoliteness is widely used in characters’ communication through multiple speech acts from the example analysis of A Dream of Red Mansions, achieving the specific purpose of the speaker and realizing the construction of powerful identity, prominent identity and affective identity.